Experimental and Computational Approaches to Interfacial Resistance in Solid-State Batteries - Takada, Kazunori; Ohno, Takahisa (Frontiers in Energy Research, 2016)
Solid-state batteries with inorganic solid electrolytes are expected to be an efficient solution to the issues of current lithium-ion batteries that are originated from their organic-solvent electrolytes. Although solid-state batteries had been suffering from low rate capability due to low ionic conductivities of solid electrolytes, some sulfide solid electrolytes exhibiting high ionic conductivity of the order of 10−2 S cm−1 have been recently developed. Since the conductivity is comparable to or even higher than that of liquid electrolytes, when taking the transport number of unity into account, ion transport in solid electrolytes has ceased from rate determination; however, it has been replaced by that across interfaces. The sulfide electrolytes show high interfacial resistance to the high-voltage cathodes. Our previous studies have demonstrated that oxide solid electrolytes interposed at the interface reduce the resistance, and they also suggest that the high resistance is attributable to a lithium-depleted layer formed at the interface. This study employs the first-principles calculation in order to gain insight into the interface. The interface structure between an oxide cathode/sulfide electrolyte simulated by the first-principles molecular dynamics has disclosed the presence of lithium-depleted layer at the interface, and the electronic structure calculated on the basis of density functional theory strongly suggests that the charge current preferentially removes lithium ions from the sulfide electrolyte side of the interface to deplete the lithium ion there. These calculation results are consistent with the transport mechanism proposed from the experimental results.